A wind tunnel investigation into the effects of roof curvature on the aerodynamic drag experienced by a light goods vehicle - Holt, Jennifer C.; Garry, Kevin P.; Velikov, S. (Inderscience, 2015)
Roof curvature is used to increase ground vehicle camber and enhance rear-body boat-tailing to reduce aerodynamic drag. Little aerodynamic data is published for light goods vehicles (LGVs) which account for a significant proportion of annual UK licensed vehicle miles. This paper details scale wind tunnel measurements at Re = 1.6 × 106 of a generic LGV utilising interchangeable roof panels to investigate the effects of curved roof profile on aerodynamic drag at simulated crosswinds between -6° and 16°. Optimum magnitudes of roof profile depth and axial location are suggested and the limited dataset indicates that increasing roof curvature is effective in reducing drag over a large yaw range, compared to a flat roof profile. This is primarily due to increased base pressure, possibly from enhanced mixing of longitudinal vortices shed from the rear-body upper side edges and increased turbulent mixing in the near-wake due to the increased effective boat-tail angle.
Keywords: Aerodynamic drag reduction; Roof curvature; Wind tunnel; LGV; Light goods vehicle; Wind averaged drag; Yaw; Boat tail